An approach to organizing the configuration of information management systems for environmental monitoring - et. al., Murtadha N. Rasol, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The problem of ecology in the world is global, therefore, scientific and practical developments in this area are complex and interdisciplinary. Search for a method for configuring an information system of environmental monitoring, depending on the view of an expert. The capabilities of information systems make it possible to develop new decision-making methods for analyzing the state of the external environment, which will allow obtaining a reliable forecast regarding their further development. The structure of information and control systems in the field of environmental monitoring, which meets the concept of configuration, is proposed. The structure of the system differs from the known ones by the presence of an intelligent module for choosing methods for processing physical data with the accumulation of experience, based on products formed by an expert. It is proposed to build modules of the data processing library based on the concept of soft computing, since this approach most fully reflects areas with a high degree of uncertainty, which include monitoring of the external environment.